Correlation of cervical cytology and visual inspection with acetic HIV-positive women (2008)
The prevalence of squamous intraepithelial lesion is higher among human immunodeficiency virus (HIV)-positive women. These lesions when they occur in these patients are also more difficult to treat. A total of 205 consenting HIV-seropositive women were recruited. A cervical cytology (Pap smear) was taken, followed by visual inspection with freshly prepared 5% acetic acid and cervical biopsy taken from the squamocolumnar junction as the reference for diagnosis to avoid verification bias. The sensitivity of VIA was 76.0% (95% CI 52.0-91.0); specificity 83.0% (95% CI 77.0-88.0); positive predictive value 34.0% (95% CI 21.0-49.0). The sensitivity of cervical cytology (Pap smear) was 57.0% (95% CI 34.0-77.0), specificity of 95.0% (95% CI 90.0-97.0), and positive predictive value of 55.0% (95% CI 33.0-75.0). In HIV-seropositive women, the sensitivity of VIA is 76.0%, making it a useful screening test for preinvasive lesion of the cervix in low resource settings.